A Model For The Adsorption Of Hydrolysable Cations On Silica - Preprint 09-131 - S. Vivek (Society for Mining, Metallurgy & Exploration, 2009)
An atomic force microscope (AFM) was used to measure the surface forces between silica surfaces immersed in solutions of hydrolysable cations and/or sodium oleate. Hydrophobic forces were observed at the pH range where the concentration of the singly-charged hydroxo-complexes (CaOH+ or MgOH+) in solution is the highest. In the absence of oleate, the adsorption of the hydroxo-complexes was indicated by the disappearance of the repulsive hydration force. These results suggest that the hydrolysable cations adsorb on silica as singly-charged hydroxo-complexes. Based on the results obtained in the present work, a model for the adsorption of hydrolysable cations has been developed.